Enhanced Biomechanical Properties of the Pectineal Ligament Support Its Reliability for Apical Pelvic Organ Prolapse Repair - Micaela Motzko; Makayla M. Swancutt; Edwin Glueck; Brandalynn Holland; Anna Stock; Zubeen Azari; Elif Diricanli; Jennifer F. Dennis; Melissa Zolnierz (Anatomia)
Pelvic organ prolapse impacts an increasing number of women in the United States. The standard approach to correcting apical pelvic organ prolapse uses the sacral anterior longitudinal ligament (SALL) to lift the vaginal apex; however, this approach may result in recurrent prolapse. A newer procedure utilizes the pectineal ligament (PL), which may be a more reliable anchor point. This study compares the biomechanical properties of these two ligaments to elucidate which can withstand more stress to provide long-term stability following prolapse. Seventeen formalin-embalmed donors were used (PL: 17 right, 16 left; SALL, 15). The PL was evaluated to better characterize the ligament’s properties within the pelvis using digital calipers and descriptive statistics. Mean values were statistically evaluated using an independent t test (p = 0.05) but no differences in laterality were appreciable. The PL and SALL samples were harvested and evaluated using a mechanical tester to determine their force at failure (N), toughness (Jm−2), and elastic modulus (MPa). The PL had increased values in the mean force at failure and toughness than the SALL when evaluated by each side as well as a combined mean value. These differences were statistically significant (p = 0.05) for toughness as evaluated using an independent t-test (right, p = 0.004; left, p = 0.005; combined, p = 0.002) and force at failure [right, p = 0.001 (independent t-test); left, p = 0.004 and combined, p = 0.005 (Mann–Whitney U test)], indicating that the PL may permit more deformation, but greater resistance to catastrophic failure as compared to the SALL. When evaluating any statistical differences in modulus, the individual and combined values were increased for the PL as compared to the SALL but were not significant (right, p = 0.290; left, p = 0.143; combined, p = 0.110) suggesting a stiffer material that may be more prone to catastrophic failure once a tear has begun. Collectively, these inherent biomechanical properties of the pectineal ligament indicate the ligament may be a more reliable anchor point for pelvic organ prolapse repair than the SALL.